Investigation of New Delhi metallo-beta-lactamase-1 (blandm-1) gene in carbapenem-resistant Enterobacterales strains isolated from a university hospital in Turkey - Merih Simsek; Cengiz Demir; Esra Seker (Medicine Science, 2021)
In this study, the presence of blaNDM-1 gene in carbapenem-resistant Enterobacterales obtained from various clinical specimen of a University Hospital in Turkey between the years 2014-2019, has been investigated. Carbapenem-resistant Enterobacterales were identified using Vitek 2. The presence of Metallo beta lactamase in these bacteria was investigated by phenotypically modified hodge test and genotypically by PCR. Of the 110 carbapenem-resistant Enterobacterales isolates, six (5.5%), 17 (15.5%) and 87 (79.0%) were identified as E. cloacae, E. coli and K. pneumoniae , respectively. While blaNDM-1gene was found in 35 (31.8%) K. pneumoniae and three (2.7%) E. coli strains, all 38 strains were found positive for blaNDM-1gene by the modified hodge test. It was determined that six E. cloacae strains did not contain the blaNDM-1 gene. Multiple antibiotic resistances were detected in carbapenem-resistant Enterobacterales strains positive for blaNDM-1. However, 29 K. pneumoniae and two E. coli strains were identified as resistant to tigecycline. Turkey also risks of the world along with other resistance enzymes and bacteria NDM-1 producing the rates must be determined globally and periodically. The fast spread of such resistant through transferable ways should not be overlooked, because enzymatic resistance genes can lead to high mortality hospital outbreaks worldwide.₀ [Med-Science 2021; 10(2.000): 571-6]